Peran Guru Ra Roihanul Jannah dalam Membentuk Karakter Islam Anak Usia Dini - Halimatus Sa`diah; Sartika Dewi Harahap (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the role of teachers at RA Roihanul Jannah in shaping Islamic character in early childhood. Early childhood education is a crucial phase in instilling fundamental Islamic values such as morality, discipline, responsibility, and worship habits. The research method used is a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that teachers have a strategic role as educators, role models, mentors, facilitators, and motivators in the process of character building. Teachers not only deliver learning materials but also instill Islamic values through daily habituation, such as collective prayers, worship practices, and polite behavior in social interactions. In addition, a conducive school environment and collaboration between teachers and parents support the success of children's character development. Learning processes integrated with Islamic values have proven effective in shaping positive behavior in children. Therefore, the role of teachers at RA Roihanul Jannah significantly influences the formation of Islamic character in early childhood in an optimal, directed, and sustainable manner in their daily lives